The distribution and abundance of cephalopods on the continental slope of the eastern South Atlantic - Roeleveld, M. A. C.; Lipiński, M. R.; Augustyn, C. J.; Stewart, B. A. (South African Journal of Marine Science, 1992)
During a cruise in March 1988 dedicated to investigation of the marine resources of South Africa's continental slope, 62 species in 22 families of Cephalopoda were collected from the Cape Canyon and Cape Point Valley. Multivariate analysis revealed a clear distinction between cephalopods of the upper and lower continental slope in both benthic and epibenthic habitats. Todaropsis eblanae and Todarodes angolensis were indicator species for the upper slope benthic, from 300 to 500 m, but on the lower slope, in 700–900 m of water, they were replaced by Histioteuthis miranda and Opisthoteuthis agassizii. In the epibenthic, both upper and lower slopes were dominated by Abraliopsis gilchristi and Lycoteuthis ?diadema, but other species characteristic of the lower slope were the oceanic species Mastigoteuthis hjorti, Ctenopteryx sicula and Taonius sp. A. Cranchia scabra indicated the presence of oceanic water at stations 700–900 m deep. Other species of significance in the catches were Todarodes filippovae, Histioteuthis macrohista, Rossia enigmatica and Bathypolypus valdiviae. Species affinities indicate that the cephalopod fauna of the southern African continental slope includes the following zoogeographic components: southern African endemic, circum-Subantarctic species associated with Antarctic Intermediate Water, circum-global southern tropical/subtropical, tropical Indo-Pacific and cosmopolitan tropical/subtropical.